CRISPR-Cas13a-Based Detection for Bovine Viral Diarrhea Virus - Yao, Rui; Xu, Yueren; Wang, Lang; Wang, Dawei; Ren, Linchang; Ren, Changling; Li, Cunyuan; Li, Xiaoyue; Ni, Wei; He, Yanhua; Hu, Ruirui; Guo, Tao; et al. (Frontiers in Veterinary Science, 2021)
Bovine Viral Diarrhea Virus (BVDV) is the main pathogen of bovine viral diarrhea disease (BVD), which lead to enormous economic loss in the cattle industry. A sensitive and specific detection for BVDV is advantageous to the control of BVDV. Clustered regularly interspaced short palindromic repeats (CRISPR)-Cas systems have been used for detecting virus RNA. In this study, the expression and purification of LwCas13a protein were optimized and the RNase activity of LwCas13a in vitro was verified. CRISPR-LwCas13a system could detect BVDV virus and BVDV RNA with high specificity and simplicity. The detection limit of the LwCas13a system was 103 pM, and there were no cross-reactions with HEK293T and MDBK. In summary, a sensitive, specific, and simple nucleic acid detection method based on CRISPR-Cas13a was developed for BVDV. This method provides a new detection strategy for early diagnosis of BVDV.